Depressive Symptom Clusters as Predictors of 6-Year Increases in Insulin Resistance: Data from the Pittsburgh Healthy Heart Project - Khambaty, Tasneem (2014)
OBJECTIVE: To examine longitudinal bidirectional associations between two depressive symptom clusters – the cognitive-affective and somatic-vegetative clusters – and insulin resistance, a marker of pre-diabetes. METHODS: Participants were 269 adults aged 50–70 years without diabetes enrolled in the Pittsburgh Healthy Heart Project, a prospective cohort study. At baseline and 6-year visits, participants completed the Beck Depression Inventory-II (BDI-II) and underwent a blood draw to quantify fasting insulin and glucose. We examined baseline BDI-II total, cognitive-affective, and somatic-vegetative scores as predictors of 6-year change in the homeostatic model of assessment (HOMA) score, an estimate of insulin resistance computed from fasting insulin and glucose. We also examined baseline HOMA score as a predictor of 6-year change in BDI-II total and subscale scores. RESULTS: Regression analyses, adjusted for demographic factors and baseline HOMA score, revealed that the baseline BDI-II somatic-vegetative score (β = .14, p = .025), but not the cognitive-affective (β = .001, p = .98) or total (β = .10, p = .11) scores, predicted 6-year HOMA change. This result persisted in models controlling for anxiety symptoms and hostility. Several factors were examined as candidate mediators; however, only change in body mass index (BMI) was a significant mediator (p = .042), accounting for 23% of the observed association. Baseline HOMA score did not predict 6-year change in BDI-II total or subscale scores (all ps >.56). CONCLUSIONS: Among adults aged 50–70 years, the somatic-vegetative symptoms of depression (e.g., fatigue, sleep disturbance, and appetite changes) may worsen insulin resistance and increase diabetes risk, partly, by increasing BMI.